Ground coffee processing a comparative study between product ZC and other commercial brands - Kraft, Erika Victoria S.
Brewed coffee has remained a desirable product despite the introduction of dried, instant, soluble coffee. As such, this study aimed to develop a standard process for the production of a ground coffee blend labelled as ZC, which can be considered competitive. The study was divided into three (3) phases which were in turn divided into subphases. Phase I dealt with the determination of best roasting temperature at a constant time. This was further divided into 3 subphases for testing three (3) coffee varieties (C. arabica, C. excelsia, and C. liberica). Phase II was divided into 2 subphases where in Phase IIA, three (3) coffee blends were evaluated for similarities to competitive products in quality. For Phase IIB, three sizes of grind were evaluated to find out the effect of particle size on quality and acceptability of coffee. Phase III, also divided into 2 subphases, aimed at determining the best coffee to water ratio for the brewing (Phase IIIA) While in Phase IIIB, the selected coffee product was compared with brands sold in local markets. The resulting products from each of the Phases were evaluated by sensory methods done either by a trained panel of judges or through the consumer-type tests. The products were later tested for physico-chemical characteristics. For Arabica coffee, roasting at 205.0°C-260.0°C for ten minutes yielded the best coffee product; for Excelsa, 149.4°C-204.4°C; and for the Liberica coffee, 205.0°C-260.0°C. All these show that the peak development of the flavor and aroma factors differed for one coffee variety to another. results from consumer-type tests and that of the trained panel indicated that a coffee blend from 50% Arabica, 25% Excelsa, and 25% Liberica ground coffee was most acceptable. Also, the smallest size of grind (0.38 mm) was found to greatly enhance the extraction of key flavor and aroma. For the brewing process, the combination of 15g coffee to 370g water was found to be the best coffee to water ratio. Finally, results of trained panel and consumer-type evaluation and by a consumer-type test that there was no significant difference between ZC and Siete Baracos. however, both ranked second to Chase and Sanborn.